Media Framing of Environmental Pollution Caused by Nickel Mining in Southeast Sulawesi on Mongabay Indonesia - Soraya, Nadia; Pratiwi, Aprilianti (International Journal of Environmental Communication (ENVICOMM), 2025)
Indonesia holds the world’s largest nickel reserves, mainly in Sulawesi and Maluku, positioning the mineral as a strategic resource for stainless-steel production and electric-vehicle battery development. Yet, the rapid expansion of nickel mining has intensified environmental problems, particularly in Southeast Sulawesi. This study examines how Mongabay Indonesia frames environmental pollution linked to nickel mining and analyzes the implications of such framing for public understanding. Through qualitative content analysis of seventeen articles published between 2023 and 2025, the study identifies dominant narratives, issue emphases, and representations of socio-ecological impacts. Guided by Entman’s (1993) Framing Theory, the findings show that Mongabay Indonesia consistently portrays nickel mining as a multidimensional environmental threat, highlighting water contamination, sedimentation, deforestation, biodiversity loss, and increasing vulnerability among coastal and Indigenous communities. The coverage frequently features community testimonies, scientific evidence, and critiques of weak regulatory enforcement. Overall, the study underscores the role of alternative environmental media in shaping discourse, amplifying affected voices, and influencing public perspectives within Indonesia’s ongoing green-energy transition.